Percutaneous Aspiration (AngioVac) of a Mitral Valve Vegetation followed by a Transcatheter Mitral Valve-in-Valve Intervention - Jack Xu; Shravan Turaga; Jay Bhama; Srikanth Vallurupalli; Gaurav Dhar (Methodist DeBakey Cardiovascular Journal)
The AngioVac transcatheter aspiration system (Angiodynamics) is used to percutaneously extract thrombi as well as vegetations typically growing from the right heart. We report a case of a failed mitral stented bioprosthesis due to a large vegetation that was treated successfully with AngioVac evacuation through a transseptal puncture followed by valve-in-valve intervention in the same setting.